Risco de crédito na securitização : análise dos determinantes do nível de disclosure dos FIDCs no Brasil - Garcia, Evelini Lauri Morri (2016)
Securitization is a capital market instrument that generates large movement of funds in the international and national levels, and in Brazil, the Investment Funds Creditório Rights (FIDC) stand out as the main securitization entities. In view of its characteristics is the presence of credit risk, with the main type of risk that investors in securitization are exposed. Accounting standards as CVM nº 489/11 and CPC 40 (R1) determine disclosure criteria that must be made so that there is asymmetry of information in the securitization market. Using the Theory of Asymmetric Information, this study aims to evaluate the disclosure level information about the credit risk in the financial statements of FIDC and identify the determinants that influence this disclosure. To meet this goal, the research used sample of 148 FIDCs standardized credits working in Brazil, in the year 2012 to 2014. It was content analysis in the notes of these funds, whose data were categorized as service level of disclosure standards and evaluated by means of statistical tests. The results indicate that the FIDC meet partially the regulatory requirements for disclosure of information about the credit risk, regardless of the regulations in which they live. There was a significant improvement as the level of disclosure of credit risk as prescription ICVM nº 489/11 over the analysis period, however, this did not occur as the normative criteria of CPC 40 (R1). A significant difference in spreading the risk as credit to aspects of normative criteria, confirming that the type of information required by the rules can be answered differently depending on the aspect you have. However, unlike previous research, credit risk disclosure level FIDCs is less qualitative normative criteria in relation to the quantitative aspects. The results also demonstrated that the disclosure of credit risk according to the guidelines of CVM Instruction nº 489/11 in the years 2013 and 2014 is influenced by the company's audit and managing entity. From the perspective of the criteria set out in CPC 40 (R1), no evidence was found that the characteristics of FIDCs influence the level of disclosure of credit risk. Therefore, the results suggest that entities have responsibility to the results and information provided by FIDCs influence the level of disclosure about the credit risk. Based on the Theory of Asymmetric Information is understood that information asymmetry exists in relation to the disclosure of credit risk by FIDC, and that factors such as the issuing body of standards, specific regulations, aspects of normative criteria and entities influential determinants are acting in their occurrence.